Ductile adhesively-bonded timber joints – Part 1: Experimental investigation. (10th August 2018) - Angelidi, Myrsini; Vassilopoulos, Anastasios P.; Keller, Thomas
Highlights: Acrylic-bonded timber joints exhibited a ductile load-displacement response in tension. Acrylic joints showed much higher ultimate loads than epoxy joints in tension. Displacement- and energy-based ductility indexes of acrylic joints were high. A strain-based quadratic failure criterion allowed to estimate the ultimate loads. Abstract: In the field of timber load-bearing structures, adhesive bonding is a promising joining technique that may increase the structural stiffness and capacity of timber joints and structures. The use of ductile adhesives may furthermore allow designing ductile joints, which can compensate for the material ductility that timber lacks. To demonstrate the potential of this approach, adhesively-bonded double-lap timber joints were manufactured using a ductile acrylic adhesive and then subjected to axial tension and compression loading. The load-displacement responses were measured and compared to those of the same joint configuration for which a brittle epoxy adhesive was used. The effect of the different adhesives on the joint capacity and ductility has been studied and quantified. Strain field measurements using the Digital Image Correlation (DIC) technique and a quadratic strain interaction criterion provided a better understanding of the mechanical behavior of the two different joint types.